A hűtlenség ára . The price of disloyalty - írta: Tóth Ernő ; szerkesztette: Szabó István. (Magyar Diafilmgyártó Vállalat, 1973)
Produced for Hungarian People's Army Financial and Methodological Centre for Political Education. The filmstrip describes the subversive tools and methods of imperialist powers used against the socialist countries during the cold war. It also warns about the dangers faced by soldiers recruited by the enemy or trying to defect. A film az imperialista hatalmaknak a szocialista országok ellen folytatott hidegháborús, fellazító tevékenységének eszközeit és módszereit, illetve a beszervezett vagy külföldre szökő katonákra leselkedő veszélyeket mutatja be.